2014
DOI: 10.2478/eces-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of various cations on the sorption of manganese in the thallus of freshwater algae spirogyra sp. and sea algae palmaria palmata

Abstract: Due to their occurrence in very different conditions and high resistance to physical and chemical factors, algae are pioneers colonising new environments and their sorption properties are used in biomonitoring and water remediation. The efficiency of the process of heavy metal sorption in algae used for in situ tests depends on abiotic factors, such as the chemical composition of water. Freshwater algae Spirogyra sp. were used in tests. Algae were exposed in the laboratory in manganese chloride solutions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…For the first step, salts in the bulk solution diffuse to the microalgae cell wall surface, and in the subsequent step, salts are deposited on the algae surface by different mechanisms, including ion exchange, microprecipitation, and complexation (coordination). , Ion exchange is considered an important mechanism for salt biosorption, as Na + can replace other cations bound to different functional groups on the algae surface. Rajfur and co-workers investigated the competitiveness of biosorption (adsorption) of different cations on the algae surface and suggested that Na + can replace Mn 2+ to be bound on the algae surface . It is worthwhile mentioning that the function of ion exchange is more related to the change of the ionic species rather than salt removal, except Na + and Cl – are replaced by H + and OH – , respectively.…”
Section: Salt Removal Mechanisms For Algae-based Desalinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first step, salts in the bulk solution diffuse to the microalgae cell wall surface, and in the subsequent step, salts are deposited on the algae surface by different mechanisms, including ion exchange, microprecipitation, and complexation (coordination). , Ion exchange is considered an important mechanism for salt biosorption, as Na + can replace other cations bound to different functional groups on the algae surface. Rajfur and co-workers investigated the competitiveness of biosorption (adsorption) of different cations on the algae surface and suggested that Na + can replace Mn 2+ to be bound on the algae surface . It is worthwhile mentioning that the function of ion exchange is more related to the change of the ionic species rather than salt removal, except Na + and Cl – are replaced by H + and OH – , respectively.…”
Section: Salt Removal Mechanisms For Algae-based Desalinationmentioning
confidence: 99%
“…Rajfur and co-workers investigated the competitiveness of biosorption (adsorption) of different cations on the algae surface and suggested that Na + can replace Mn 2+ to be bound on the algae surface. 58 It is worthwhile mentioning that the function of ion exchange is more related to the change of the ionic species rather than salt removal, except Na + and Cl − are replaced by H + and OH − , respectively. Microprecipitation occurs if the Na + solubility limit is reached.…”
Section: ■ Introductionmentioning
confidence: 99%